Adaptive synchronous tracking control for n-PPPS redundantly actuated distributed parallel manipulators with dynamic uncertainties - Liang, Sen; Han, Bing; Wang, Xinfeng; Zhou, Xinfang; Fang, Qiang; Wei, Yanding (Control engineering practice, 2025)
Redundantly actuated distributed parallel manipulators (RADPMs) are widely used for posture alignment and assembly of large-scale components. The structural characteristics of multiple redundant actuation chains not only possess potential advantages, but also bring about challenges for multi-joint coordinated motion. To address the synchronization control issue of the system with dynamic uncertainties, a novel adaptive synchronous tracking control (ASTC) scheme is proposed to realize high-precision trajectory tracking and coordination performance simultaneously. In the proposed ASTC scheme, a synchronization error is first introduced to depict the coordination relationship between adjacent joints and coupled with the tracking error to form a composite error in the joint space. Based on the defined errors, a dual-space adaptation law is proposed through the linear parameterized expression of the system dynamic model to obtain feedforward compensation for dynamics. Additionally, in order to restrain the influence of inevitable external disturbances, a robust control compensation term is introduced to improve the disturbance rejection ability. Moreover, the stability of the entire closed-loop system is proved by utilizing the Lyapunov theory. Finally, simulation and experiments are conducted on an actual 4-PPPS RADPM, and the comparative results demonstrate that the proposed scheme can effectively improve the tracking accuracy and synchronization performance of the system. •An adaptive synchronous tracking control scheme is proposed for parallel manipulators.•The control scheme enhances the coordination of redundant actuation joints.•Uncertain dynamic parameters and unmodeled disturbances are taken into account.•The effectiveness of the scheme is verified through simulation and experiments.